Demographic, lifestyle, and other factors in relation to antimüllerian hormone levels in mostly late premenopausal women - Jung, S; Allen, N; Arslan, A; Baglietto, L; Brinton, L; Egleston, B; Falk, R; Fortner, R; Helzlsouer, K; Idahl, A; Kaaks, R; Lundin, E; et al. (Elsevier, 2017)
OBJECTIVE: To identify reproductive, lifestyle, hormonal, and other correlates of circulating antimüllerian hormone (AMH) concentrations in mostly late premenopausal women. DESIGN: Cross-sectional study. SETTING: Not applicable. PATIENT(S): A total of 671 premenopausal women not known to have cancer. INTERVENTION(S): None. MAIN OUTCOME MEASURE(S): Concentrations of AMH were measured in a single laboratory using the picoAMH ELISA. Multivariable-adjusted median (and interquartile range) AMH concentrations were calculated using quantile regression for several potential correlates. RESULT(S): Older women had significantly lower AMH concentrations (≥40 [n = 444] vs. <35 years [n = 64], multivariable-adjusted median 0.73 ng/mL vs. 2.52 ng/mL). Concentrations of AMH were also significantly lower among women with earlier age at menarche (<12 [n = 96] vs. ≥14 years [n = 200]: 0.90 ng/mL vs. 1.12 ng/mL) and among current users of oral contraceptives (n = 27) compared with never or former users (n = 468) (0.36 ng/mL vs. 1.15 ng/mL). Race, body mass index, education, height, smoking status, parity, and menstrual cycle phase were not significantly associated with AMH concentrations. There were no significant associations between AMH concentrations and androgen or sex hormone-binding globulin concentrations or with factors related to blood collection (e.g., sample type, time, season, and year of blood collection). CONCLUSION(S): Among premenopausal women, lower AMH concentrations are associated with older age, a younger age at menarche, and currently using oral contraceptives, suggesting these factors are related to a lower number or decreased secretory activity of ovarian follicles.